Intersections: cultures, sexualités et genres - Brotman, Shari L.; Lévy, Joseph J. (Collection Santé et société, 2008)
Les intersections entre la culture, le genre et la sexualité retiennent aujourd’hui l’attention des chercheurs qui travaillent sur la diversité sexuelle, une tendance que l’on rencontre dans l’espace québécois et canadien. Plusieurs études ont ainsi porté sur ces enjeux parmi les autochtones et les groupes ethnoculturels. Cet ouvrage collectif, réalisé par des chercheurs, anglophones et francophones, de l’équipe pancanadienne Sexualités, Vulnérabilités et Résilience, présente ainsi un ensemble de travaux qui font le point sur ces questions. Les dimensions théoriques et méthodologiques sont ainsi cernées et des études empiriques, faisant appel à des approches quantitatives et qualitatives, traitent des trajectoires et des identités parmi différentes populations, des problèmes de santé auxquels elles peuvent être confrontées et des variations dans les usages sociosexuels d’Internet. Ce tour d’horizon aide à mieux comprendre la complexité des intersections touchant les identités sexuelles et les dimensions culturelles et suggère des pistes de recherche et d’intervention à développer.
Keywords: 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; amériques; approches et analyses; canada; cours; discipline; identités LGBTQIA2+; intersectionnalité; premier cycle; psychologie; périodes historiques; queer; québec; ressource en ligne; régions géographiques; sciences humaines; sciences sociales; sex2283; sexologie; sexualité; thématiques; travail social

Sexual Attitudes and Double Standards: A Literature Review Focusing on Participant Gender and Ethnic Background - Fugère, Madeleine A.; Escoto, Carlos; Cousins, Alita J.; Riggs, Matt L.; Haerich, Paul (Sexuality & Culture : An Interdisciplinary Quarterly, 2008)
We conducted a review of literature regarding sexual attitudes and double standards, focusing on participant gender and ethnic background. We found that men had more permissive sexual attitudes than women, and that African Americans had the most permissive sexual attitudes, followed by White Americans, then by Hispanic Americans and Asian Americans. The literature regarding sexual double standards was mixed; some studies showed evidence of continued sexual double standards and some studies showed the absence of sexual double standards. In some studies, men were more likely to endorse the sexual double standard than women. We found only one article addressing sexual double standards using ethnic background as a quasi-independent variable; this research revealed that non-North American (Russian and Japanese) samples were more likely to endorse the traditional double standard, that sex is more acceptable for men than for women.
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; asie; cours; discipline; europe; japon; premier cycle; psychologie; périodes historiques; rapports sociaux de sexe; ressource en ligne; russie; régions géographiques; sciences humaines; sciences sociales; sex2283; sexisme; sexologie; sexualité; systèmes d'oppressions; thématiques; états-unis

The affective turn: Theorizing the social - Clough, Patricia Ticineto; Halley, Jean (Duke University Press, 2007)
In the mid-1990s, scholars turned their attention toward the ways that ongoing political, economic, and cultural transformations were changing the realm of the social, specifically that aspect of it described by the notion of affect: pre-individual bodily forces, linked to autonomic responses, which augment or diminish a body’s capacity to act or engage with others. This “affective turn” and the new configurations of bodies, technology, and matter that it reveals, is the subject of this collection of essays. Scholars based in sociology, cultural studies, science studies, and women’s studies illuminate the movement in thought from a psychoanalytically informed criticism of subject identity, representation, and trauma to an engagement with information and affect; from a privileging of the organic body to an exploration of nonorganic life; and from the presumption of equilibrium-seeking closed systems to an engagement with the complexity of open systems under far-from-equilibrium conditions. Taken together, these essays suggest that attending to the affective turn is necessary to theorizing the social.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; corps; discipline; identités; périodes historiques; représentations; sciences humaines; sciences sociales; sociologie; thématiques; traumatismes; émotions

Itinéraires d'égalités. Trajectoires des femmes autochtones du Québec et du Canada - Levesque, Carole; Labrecque, Marie France (30e anniversaire de l’Association des Femmes Autochtones du Québec, 2007)
À l’occasion du 30e anniversaire de l’Association des Femmes autochtones du Québec, ces actes de colloque proposent de revoir le parcours des femmes autochtones dans leurs luttes pour l’égalité et la justice sociale.
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; canada; cours; discipline; droits des femmes*; environnement; féminisme autochtone; histoire et politique; inégalités; justice sociale; mexique; militance; pol4105; premier cycle; pédagogie; périodes historiques; québec; ressource en ligne; régions géographiques; sciences humaines; sciences sociales; système colonial; systèmes d'oppressions; thématiques; violences; études autochtones

Rocking Sexualities: Iranian Migrants' Views on Sexuality - Ahmadi, Nader (Archives of Sexual Behavior : The Official Publication of the International Academy of Sex Research, 2003)
The purpose of this article is to put forward a theoretical discussion about Islamic views of sexuality and by means of an example show how Iranian immigrants in Sweden view sexuality and sexual culture. Building on theories that compare individualistic and holistic ways of thinking, the article seeks to elucidate the impact of basic cultural qualities on the formation of sexualities. The conclusion of the article is that the encounter with the Swedish way of thinking and the Swedish sexual culture seems to have influenced Iranian migrants' views on the nature of the relationship between couples and sexual decision making within the relationship. Exposed to an individualistic ideology and lifestyle in Sweden, Iranian migrants show a clear tendency to revise their previous holistic way of thinking, especially in regard to sexuality: the traditional, authoritarian, patriarchal sexual relationship among Iranian migrants in Sweden is giving way to more egalitarian relationships, and a relatively strong tendency towards a similarity of views between the sexes regarding sexuality can be observed. The most important change that could be observed in regard to the respondents in the study is probably an increased individualism.
Keywords: 2000 à aujourd'hui; 2000-2009; approches et analyses; asie; cours; discipline; europe; inégalités; iran; patriarcat; premier cycle; périodes historiques; rapports sociaux de sexe; ressource en ligne; régions géographiques; sciences humaines; sciences sociales; sex2283; sexisme; sexualité; suède; systèmes d'oppressions; thématiques; travail social

The fourth world: an indigenous perspective on feminism and aboriginal women's activism - Ouellette, Grace Josephine Mildred Wuttunee (Basics from Fernwood Publishing, 2002)
"This book is not about feminism. Rather, feminism is the basis of the discussion, an example of how understanding oppression must consider a number of barriers. Euro-Canadian feminists rarely address the circumstances that are unique to First Nations' women, instead working with the assumption that all women are a part of a similar struggle. Ouellette attempts to confront these barriers. Throughout interviews with a number of women, she highlights the following four questions. To what extent do Aboriginal women understand experience and articulate their oppression? To what extent do colonized women perceive racism as the source of their oppression? To what extent do Aboriginal women view male domination within their own Aboriginal societies as the source of the oppression? How do Aboriginal women articulate racism and gender oppression?The author argues that there will always be a dichotomy between European and Aboriginal thought. This book makes an important contribution toward a greater understanding of Aboriginal thought and an Aboriginal perspective on society. The Fourth World theory is an integrate part of the "Circle of Life" philosophy of Aboriginal people. In keeping with oral traditions, these teachings are passed on at gatherings and in private conversations. They compromise a distinctly Aboriginal worldview."
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; canada; cours; discipline; féminisme autochtone; histoire et politique; inégalités; pol4105; premier cycle; périodes historiques; racisme; régions géographiques; saskatchewan; sciences humaines; sciences sociales; sexisme; système colonial; systèmes d'oppressions; thématiques; études autochtones